2018
DOI: 10.1016/j.concog.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Are morally good actions ever free?

Abstract: Research has shown that people ascribe more responsibility to morally bad actions than both morally good and neutral ones, suggesting that people do not attribute responsibility to morally good actions. The present work demonstrates that this is not so: People ascribe more free will to morally good than neutral actions (Studies 1a-1b, Mini Meta). Studies 2a-2b distinguished the underlying motives for ascribing freedom to morally good and bad actions. Free will ascriptions for immoral actions were driven predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 90 publications
3
20
0
Order By: Relevance
“…Implications and Directions for Future Research The findings reported in this paper have theoretical implications for both the psychology of free will belief and political psychology. First, these findings provide further and more direct support for previous work conducted on free will belief as motivated social cognition (Clark, Baumeister, et al, 2017;Clark et al, 2014;Clark, Shniderman, et al, 2018;Clark, Winegard, & Baumeister, 2019;Vonasch et al, 2017). The work reported here demonstrates that belief in free will is linked to a desire to hold people accountable for their moral wrongdoing, and that free will attributions vary as a function of the valence of the action, how moral or immoral it is perceived to be, and even who the target is.…”
Section: Overview Of Findingssupporting
confidence: 81%
“…Implications and Directions for Future Research The findings reported in this paper have theoretical implications for both the psychology of free will belief and political psychology. First, these findings provide further and more direct support for previous work conducted on free will belief as motivated social cognition (Clark, Baumeister, et al, 2017;Clark et al, 2014;Clark, Shniderman, et al, 2018;Clark, Winegard, & Baumeister, 2019;Vonasch et al, 2017). The work reported here demonstrates that belief in free will is linked to a desire to hold people accountable for their moral wrongdoing, and that free will attributions vary as a function of the valence of the action, how moral or immoral it is perceived to be, and even who the target is.…”
Section: Overview Of Findingssupporting
confidence: 81%
“…In line with this, individuals who commit negative acts receive higher judgements of free will and responsibility compared to individuals who commit positive acts (Feldman, Wong, & Baumeister, 2016;Hamlin & Baron, 2014;Knobe, 2003;Morewedge, 2009). Worth noting, individuals who commit positive actions are given higher responsibility and conscious will attributions compared to those who commit morally neutral actions (Clark et al, 2014;Clark et al, 2018). This implies that heroes are given some portion of responsibility.…”
Section: Rewardmentioning
confidence: 75%
“…Are a hero's actions viewed differently if the behavior arises from a source other than the actor's own conscious will (as may be the case with criminals)? Clark et al (2018) suggests that there may be a positive relationship between higher conscious will attributions and reward judgements, such that we give higher rewards to heroes who have conscious will. However, this…”
Section: Rewardmentioning
confidence: 99%
“…In line with this, individuals who commit negative acts receive higher judgements of free will and responsibility compared to individuals who commit positive acts (Feldman, Wong, & Baumeister, 2016;Hamlin & Baron, 2014;Knobe, 2003;Morewedge, 2009). Worth noting, individuals who commit positive actions are given higher responsibility and conscious will attributions compared to those who commit morally neutral actions Clark et al, 2018). This implies that heroes are given some portion of responsibility.…”
Section: Rewardmentioning
confidence: 99%
“…Are a hero's actions viewed differently if the behavior arises from a source other than the actor's own conscious will (as may be the case with criminals)? Clark et al (2018) suggests that there may be a positive relationship between higher conscious will attributions and reward judgements, such that we give higher rewards to heroes who have conscious will. However, this possibility has yet to be experimentally investigated.…”
Section: Rewardmentioning
confidence: 99%